Survival Comparison of Neoadjuvant Chemotherapy Followed by Irreversible Electroporation Versus Conversional Resection for Locally Advanced Pancreatic Cancer - He, Chaobin; Sun, Shuxin; Huang, Xin; Zhang, Yu; Lin, Xiaojun; Li, Shengping (Frontiers in Oncology, 2021)
Locally advanced pancreatic cancer (LAPC) is a lethal disease and neoadjuvant chemotherapy and conversional resection is shown to provide the best survival for LAPC patients. Irreversible electroporation (IRE) is a new and effective method for the treatment of LAPC. This study aimed to compare the long-term survival of LAPC patients after neoadjuvant chemotherapy followed by conversional resection and IRE. A total of 140 LAPC patients were included from August 2015 to March 2020. The survival outcomes of patients after treatment with chemotherapy, chemotherapy combined with conversional resection or IRE were analyzed and compared. Patients in these three groups had similar clinical and pathological characteristics. Patients in the resection and IRE groups had similar median OS time (resection group vs. IRE group: 25.3 months vs. 26.0 months, P>0.050), which was significantly longer than that of the chemotherapy group (8.7 months, P<0.001). Additionally, patients in the resection and IRE groups had a median PFS of 10.6 and 12.0 months, respectively. Also, they were significantly higher than that of patients in the chemotherapy group. Chemotherapy combined with conversional resection and IRE was identified as significant prognostic factors for OS and PFS in LAPC patients. It was shown that compared with neoadjuvant chemotherapy followed by surgical resection, chemotherapy and IRE provided similar OS and PFS for LAPC patients with minimal invasion. This combination therapy may be a suitable treatment for LAPC patients.